2020
DOI: 10.1007/s00701-020-04652-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgery and coronavirus: impact and challenges—lessons learnt from the first wave of a global pandemic

Abstract: Introduction and objectives The novel severe acute respiratory syndrome coronavirus 2 (COVID-19) pandemic has had drastic effects on global healthcare with the UK amongst the countries most severely impacted. The aim of this study was to examine how COVID-19 challenged the neurosurgical delivery of care in a busy tertiary unit serving a socio-economically diverse population. Methods A prospective single-centre cohort study including all patients referred to the acute neurosurgical service or the subspecialty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…We present and analyze a series of ten patients undergoing neurosurgical procedures, while suffering from a concomitant COVID-19 infection. To our knowledge, this is one of a few case series specifically focusing on COVID-19-positive patients undergoing neurosurgical operations [12,13]. In this series, we observed thrombotic and hemorrhagic complication rates of 30% and 20%, respectively; however, none of these studies focused on neurosurgical patients [12].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We present and analyze a series of ten patients undergoing neurosurgical procedures, while suffering from a concomitant COVID-19 infection. To our knowledge, this is one of a few case series specifically focusing on COVID-19-positive patients undergoing neurosurgical operations [12,13]. In this series, we observed thrombotic and hemorrhagic complication rates of 30% and 20%, respectively; however, none of these studies focused on neurosurgical patients [12].…”
Section: Discussionmentioning
confidence: 76%
“…It has been shown that patients undergoing general surgery with a concomitant COVID-19 infection are prone to developing postoperative complications [12]. To our knowledge, several studies have focused on the changes in referrals and organization of neurosurgical units during the SARS-CoV-2 pandemic but only few studies have investigated the incidence of perioperative complications in patients undergoing cranial neurosurgical procedures with concomitant COVID-19 infection [13][14][15][16]. This study aimed to investigate the rate of perioperative hemorrhagic or thrombotic complications in SARS-CoV-2-positive patients undergoing neurosurgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…This was indeed one of the negative consequences the first wave of the COVID-19 pandemic instigated, with mandatory delays and cancellations in elective surgeries, that translated into a 3-month unnecessary corticosteroid therapy in this patient. 13 As a consequence, this patient developed opportunistic infections which eventually led to septicaemia and despite the initially excellent neurological recovery, the patient’s death.…”
Section: Discussionmentioning
confidence: 98%
“…The COVID-19 pandemic has affected the running of neurosurgical services worldwide, with varying effects seen. Some services have noted no change in their volume [2], or an increase in emergency procedures performed [3]. Other centres have seen a reduction in procedures and admissions [4][5][6].…”
Section: Discussionmentioning
confidence: 99%